Biocatalysis Fueled by Light: On the Versatile Combination of Photocatalysis and Enzymes. (17th July 2019) - Seel, Catharina J.; Gulder, Tanja
Abstract: Enzymes catalyze a plethora of highly specific transformations under mild and environmentally benign reaction conditions. Their fascinating performances attest to high synthetic potential that is often hampered by operational obstacles such as in vitro cofactor supply and regeneration. Exploiting light and combining it with biocatalysis not only helps in overcoming these drawbacks, but the fruitful liaison of these two fields of "green chemistry" also offers opportunities to unlock new synthetic reactivities. In this review we provide an overview of the wide variety of photo‐biocatalysis, ranging from the photochemical delivery of electrons required in redox biocatalysis and photochemical cofactor and reagent (re)generation to direct photoactivation of enzymes enabling reactions unknown in nature. We highlight synthetically relevant transformations such as asymmetric reactions facilitated by the combination of light as energy source and enzymes' catalytic power. Abstract : Shine a light on biocatalysis : This review highlights recent advances in the field of photo‐biocatalysis, emphasizing the synthetic relevance of the reactions performed. Different fields of photo‐biocatalysis are covered, ranging from mediated and non‐mediated transfer of light‐induced electrons to enzymes, reagent supply, and whole‐cell approaches to photoenzymes and the generation of new enzymatic reactivity with the aid of irradiation.